Respuesta :
Hello!
1. Distribute the -2 to both terms in the parentheses.
-2x+6
2. Set the equation equal to 0 & solve for x.
-2x+6=0
3. Subtract 6 from both sides.
-2x=-6
4. Divide both sides by -2 to solve for x.
x=3
There’s your answer, x=3! :)
1. Distribute the -2 to both terms in the parentheses.
-2x+6
2. Set the equation equal to 0 & solve for x.
-2x+6=0
3. Subtract 6 from both sides.
-2x=-6
4. Divide both sides by -2 to solve for x.
x=3
There’s your answer, x=3! :)
Answer:
Distribute the -2
-2x+6
Make equation equal to 0
-2x+6 = 0
Then solve for x since that will be your solution
Step-by-step explanation: